The pros and cons of supervised urine tests in opioid replacement therapy : A study of patients' experiences - Monwell, Bodil; Bülow, Per; Johnson, Björn ; 0000-0002-1601-2706 (Heroin Addiction and Related Clinical Problems, 2018)
Background: In opioid replacement therapy (ORT), drug testing is performed continuously to ensure that patients are taking their prescribed medication, and to detect whether they have taken other, non-prescribed, substances. Typically, supervised urine testing is conducted, and in Sweden such testing is often an ORT precondition. Aim: This study investigates ORT patients’ experiences of and views on supervised urine testing. Methods: Structured interviews were conducted with 90 Swedish ORT patients. During the interview, patients were asked to say what they thought about the supervised urine tests required. The answers were then analysed through content analysis. Results: Three main themes with sub-themes were found in the patients’ statements. 1) The consequences of the test results (sub-themes: external control can provide assurance; proven drug intake may have negative consequences for patients; proven drug abstinence can yield advantages for patients), 2) The testing procedures (sub-themes: supervised urine testing is humiliating and causes harm; how you are treated is important; clinical culture and attitudes differ; stress, pressure and anxiety – tests can be difficult to perform), and 3) The structure of the testing (sub-themes: structure is needed in life; inflexible testing schemes can interfere with treatment goals; gathering people with similar problems can be counterproductive). Conclusions: Most interviewees found the testing functional as support or as proxy control in case of personal loss of control. However, supervised urine testing also constitutes a severe invasion of privacy. Less demeaning testing methods need to be developed and implemented.
2023-12-18T13:23:19.197+01:00
Keywords: methadone; buprenorphine; opioid replacement therapy; opioid substitution treatment; supervised; urine test; Social Sciences; Samhällsvetenskap